PENERAPAN MODEL PEMBELAJARAN LANGSUNG DENGAN REMEDIAL MELALUI TUTOR SEBAYA UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA - Nisaul Lifty Wardani, ; Kasron, (Pendidikan Ekonomi, 2012)
This research is aimed to know the implementation of direct learning by remedial trough the peer teaching to the teacher activity, student activity, learning comprehensiveness The subject of this research is the XI Social 1 class in SMA Negeri 1 Kraksaan year 2011/2012. This study applies the class action research that done in two cycles. The study shows that the teacher activity is increased based on the acquired average score which is increased form the first cycle to the second cycle, that is 3,6 (fair); and 4,23 (good). Whereas the student activity shows 3,38 (fair) and 4,00 (good) in the second cycle. The classical comprehensiveness result in the first cycle is 93,94% and 100% in the second cycle. In other words, the classical comprehensiveness is reached and increased. The students positively response the model, it is proved by the number of agreed student dealt with the method applied is 84,84%.